GLOBALISASI, NEO-LIBERALISME DAN ANCAMAN DEHUMANISASI - Mutiullah Mutiullah (UIN Sunan Kalijaga Yogyakarta, 2016)
It is an interesting thing to explore globalization as an era of trade growth between nations and a massive single economic system that is universal today. The single system is called neo-liberalism, which is a system that promotes increasing profits by the way of the free market. This system is expected to eliminate economic disparities between continents, nations, races, ethnics and languages inshared prosperity. The negative effects of globalization and neo-liberalism are not local or regional issues, on the other hand, globalization and neo-liberalism 'monster' that are ready to exterminate anyone who gets in his desire. Nevertheless, the analysis of class conflict for today is increasingly unclear; however, the class war is shifted increasingly wider into State class. This is the urgency of the studies in this paper tries to analyse globalization, neo-liberalism and the threat of dehumanization of human life in this modem era.